Innovative Artificial Agro‐Ecosystems Enhance Soil Carbon Sequestration in Coastal Zones of Southeast China. Issue 6 (6th February 2013) - Zhao, Gengmao; Sun, Xing; Ling, Liu; Liu, Zhaopu
Abstract Tidal flats, which are important reserved land resources, have a vital role in climate change. To evaluate the contribution of coastal saline soils to carbon sequestration, field tests were performed over a 3 year period at the Dafeng Wanggang Experimental Station in Jiangsu Province, China. Six artificial agro‐ecosystems, including wasteland (WL), freshwater fish culture (FC), Sesbania culture (SC), barley culture (BC), mixed culture of fish and Sesbania (MCFS) and mixed culture of fish and barley (MCFB), were established according to developmental processes of coastal saline soils. At the initial stage of tidal flat reclamation, the soil organic carbon (SOC) increased by 59.4 t ha−1 in the FC system during 3 years, which was much higher than that of the WL system (40.7 t ha−1). When the tidal flats evolved into high saline soils, the MCFS system sequestered SOC more effectively than the FC or SC systems with increases of 53.1, 16.9 and 8.3 t ha−1, respectively. Subsequently, in the low saline soils, the maximum soil carbon sequestration was obtained in the MCFB system (35.8 t ha−1) followed by the BC (17.5 t ha−1) and FC (13.5 t ha−1) systems. Therefore, proper development of tidal flats to farmland and the subsequent establishment of optimised artificial agro‐ecosystems make an important contribution to carbon sequestration and climate changes in coastal areas.